Indoor Thermal Environment in Tropical Climate Residential Building - Jamaludin, N. (EDP Sciences, 2014)
Indoor thermal environment is one of the criteria in sustainable building. This criterion is important in ensuring a healthy indoor environment for the occupants. The consideration of environmental concerns at the early design stage would effectively integrate the sustainability of the building environment. Global climate changes such as global warming do affect human comfort since people spend most of their time and activities in the building. The increasing of urban population required additional housing for households, as well as places to shop, office and other facilities. Occupants are now more conscious the importance of sustainability for a better quality of life. Good thermal environment is essential for human wellness and comfort. A residential environment will influence residents' health and safety. The global warming increase the earth's temperature and greenhouse emission to the atmosphere cause adverse effects to the outdoor environment. Residential developments modify the materials, structure and energy balance in urban climate effects of human economic activities. As an indoor environment is influenced by the outdoor condition, the factors affecting indoor thermal environment are crucial in improving a comfortable and healthy environment in residential building. The microclimatic of a site such as temperature and relative humidity, and wind movement led to the variation of indoor thermal environment in the building. Â© 2014 Owned by the authors, published by EDP Sciences.